PENINGKATAN KESANTUNAN BERBAHASA ANAK USIA DINI MELALUI PEMBIASAAN UCAPAN SANTUN DI TAMAN KANAK-KANAK ZAHARA KOTA BENGKULU - Suryani, Neni; Marlina, Serli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Language politeness is an important element in the socio-developmental trajectory of early childhood. However, many children enrolled at Zahara Kindergarten, located in Bengkulu City, demonstrate a lack of adherence to socially acceptable linguistic behavior in their daily interactions. This investigation seeks to improve children's linguistic abilities through systematic familiarization with appropriate politeness. This study used the Class Action Research (CAR) methodology, which was implemented in two cycles with child participants from group B, aged 5 to 6 years. Data were collected through various methods including observation, documentation, and assessment checklists, then subjected to quantitative descriptive analysis. The results showed that the habituation of polite speech effectively improved children's language politeness. In the pre-cycle, children who were in the Not Developing (BB) category were 72.73%. After the action in the first cycle, the Developing According to Expectations (BSH) category reached 45.46% and the Developing Very Well (BSB) category 18.9%. In the second cycle, the Developing Very Well (BSB) category increased to 90.91%. Thus, the habit of polite speech has been proven to be effective in increasing the politeness of language in early childhood.